Viability analysis of pine sawdust drying in a fountain dryer - Rojcewicz, Konrad; Oksiuta, Zbigniew (Technical Sciences, 2020)
The article presents analysis of physicochemical properties of pine sawdust originating from the area of the Knyszyńska Forest, in the context of possibility of their drying in a fountain dryer. Number of tests were carried out on dry pine chips of 45% moisture, such as: chemical composition, calorific value, ash content as well as morphological changes of dried material. The water storage mechanism in chips and the mechanism of formation of a fountain bed were also discussed. Based on the obtained results, several technical solutions and modifications of the fountain dryer were proposed. These modifications enable the sawdust of heterogeneous size and shape to be dried in a fountain drier as well as additional functional properties.